Specyfika wpływu Kościoła Katolickiego na życie polityczne w Polsce - Witkowska, Jadwiga (My University, 2013)
W pracy w skrócie przedstawione zostały relacje państwo – Kościół katolicki po drugiej wojnie światowej aż do roku 2010. W przeciągu kilkudziesięciu lat, rola Kościoła zmieniała się w zależności od tego jaka była sytuacja polityczna w kraju. Rozdział pierwszy i rozdział drugi to charakterystyka - skrótowy opis tego czym jest religia, wiara, chrześcijanin i jaka jest specyfika polskiego katolicyzmu. Jak religia Kościoła katolickiego wpływa na zachowania Polaków w życiu codziennym i w relacjach z innymi. W rozdziałach tych pod uwagę została wzięta również rola i pozycja duchowieństwa (hierarchów kościelnych) w funkcjonowaniu w rożnych warunkach politycznych. Rozdział trzeci to ogólne omówienie tożsamości Kościoła po drugiej wojnie światowej, aż do przemian ustrojowych w 1989 r. Podkreślona została tutaj ogromna rola Kościoła katolickiego, który był pewnego rodzaju „parasolem ochronnym” w czasach dominacji komunistycznej i jaką spełniał rolę kiedy strona rządowa i związkowa (Solidarność) usiadły do wspólnych rozmów. Rozdział czwarty w większej części poświęcony jest wydarzeniom w 2010 r. Zwłaszcza tym co działo się w Polsce i z Polakami po śmierci Jana Pawła II i po tragedii smoleńskiej i jak te wydarzenia wpłynęły na wyniki wyborów parlamentarnych i prezydenckich.

This work presents in brief the relationship between the State and the Catholic Church after the Second World War until 2010. For the past several years, the role of the church has changed depending on the political situation in the country. Chapter One and Chapter Two is a characteristic - a brief description of what is religion, faith, Christian and what is the specificity of Polish Catholicism. These chapters also describe how religion of the Catholic Church affects the behavior of Poles in everyday life and relationships with others. These chapters have also been taken into account the role and position of the clergy (Church officials) in different political conditions. The third chapter is a general overview of the identity of the church after the Second World War up to the constitutional changes in 1989. This chapter emphasizes the important role of the Catholic Church which was a kind of ‘protective umbrella' during Communist domination as well as its role when the government and the trade unions (Solidarity) sat down to common conversation. The fourth chapter in the greater part is devoted to the events in 2010, especially to what has happened in Poland and with the Poles after the death of John Paul II and the tragedy of Smolensk, and how these events have affected the results of the parliamentary and presidential elections.
The specificity of the Catholic Church influence on the political life in Poland
Keywords: kościół; państwo; wpływ; tożsamość; polityka; relacja; church; state; influence; identity; politics; relations